Representasi Sosial Budaya Suku Ambai dalam Cerita Rakyat: The Social Representation of The Ambai Tribe in Ambai’s Folklores - Esther Rita Embram (Kibas Cenderawasih : Jurnal Ilmiah Kebahasaan dan Kesastraan, 2021)
The folktale of Ambai is a cultural product that were contain of values. Socio-culture that are reflects of the speaking community, such as the mindset, belief system, social system, philosophy of life of the Ambai people. The expressions and symbols in the Ambai folktale are socio-cultural representations of the Ambai community related to their socio-cultural educational values. The socio-cultural representation of the Ambai tribe is contained in seven cultural elements according to Koentjaraningrat, namely religion and religious ceremonies, social systems, knowledge systems, language systems, living equipment systems, livelihood systems, and arts. This research is a qualitative research using sociological literary approach with a review of the meaning of representation based on Sumarjo's opinion. The presence of researchers in this study are as a key instrument. The activity carried out by the researcher was reading text, identify, codify, classify, and interpret or interpreting data, which is sourced from Ambai folktale texts.